Molecular features toward high photo-CIDNP hyperpolariztion explored through the oxidocyclization of tryptophan. Issue 11 (12th March 2021) - Torres, Felix; Sobol, Alexander; Greenwald, Jason; Renn, Alois; Morozova, Olga; Yurkovskaya, Alexandra; Riek, Roland
Abstract : Photo-chemically induced nuclear polarization yields to NMR signal-to-noise enhancement and can be tuned by chemical modification of one of the radical-pair partners. Abstract : Photo-chemically induced dynamic nuclear polarization (photo-CIDNP) is a promising solution to the inherent lack of sensitivity in NMR spectroscopy. It is particularly interesting in biological systems since it operates in water, at room temperature, and it can be repeated if the bleaching of the system can be controlled. However, the photo-CIDNP signal enhancement is well below those of other hyperpolarization techniques. While DNP, PHIP, and SABRE reach polarization enhancements of 10 3 to 10 4 -fold, photo-CIDNP enhancement is typically only one order of magnitude for 1 H and two orders of magnitude for 13 C in the amino-acids tryptophan and tyrosine. Here we report on a photo-oxidation product of tryptophan that is strongly photo-CIDNP active under continuous wave light irradiation. In conjunction with the dye Atto Thio 12, a 1 H signal enhancement of 120-fold was observed on a 600 MHz spectrometer, while at 200 MHz the enhancement was 380-fold. These enhancements in signal to noise correspond to a reduction in measurement time of 14 400-fold and 144 400-fold, respectively. The enhancement for 13 C is estimated to be over 1200-fold at 600 MHz which corresponds to an impressive measurement time reduction of 1 440 000-fold. This photo-CIDNP active oxidation product of tryptophan has been identified to be 3α-hydroxypyrroloindole. The reasons for its improved signal enhancement compared to tryptophan have been further investigated.